The Effect of addition different levels of katuk leaf meal in the ration on cholesterol, triglyceride, LDL, and HDL of broiler blood - Kamalia, .; Mujnisa, Andi; Natsir, Asmuddin (Universitas Hasanuddin, 2014)
The aims experiment were to study the effect of adding different levels of katuk meal on the levels of cholesterol,triglycerides,LDL,and HDL in the blood of broiler chiken. Sixty four (64) treatment diets according to completely randomized design. The treatment diets were :P0 = contol, P1 = control + 1 % katuk leaf meal, P2 = Control + 2% katuk leaf meal, P3 = control + 3 % katuk leaf meal. The replication for each treatment was four giving total number of experimental diet was 16. Control ration consisted of brn, yellow cron, coconut oil, shrimp waste, fish meal, tofu dregs, soy bean. During the experiment broiler chiken ware given a free access to drinking water. The resuls of study indicated that addition of katuk leaf meal into the diet did not affect concentration of cholesterol, triglycerides, and LDL in the blood of broiler. But significantly increased the concentration of blood HDL but had no effects on concenetration of blood cholesterol, blood triglycerides, and blood LDL of broiler.